Hablo Inglés y Español: Cultural Self-Schemas as a Function of Language - Rodríguez-Arauz, Gloriana; Ramírez-Esparza, Nairán; Pérez-Brena, Norma; Boyd, Ryan L. (Frontiers in Psychology, 2017)
Research has demonstrated that bilingual individuals experience a “double personality”, which allows them to shift their self-schemas when they are primed with different language modes. In this study, we examine whether self-schemas change in Mexican-American (N=193) bilinguals living in the U.S. when they provide open-ended personality self-descriptions in both English and Spanish. We used the Meaning Extraction Helper (MEH) software to extract the most salient self-schemas that influence individuals’ self-defining process. Following a qualitative-inductive approach, words were extracted from the open-ended essays and organized into semantic clusters, which were analyzed qualitatively and named. The results show that as expected, language primed bilinguals to think about different self-schemas. In Spanish, their Mexican self-schemas were more salient; whereas, in English their American self-schemas were more salient. Similarities of self-schemas across languages were assessed using a quantitative approach. Language differences and similarities in theme definition and implications for self-identity of bilinguals are discussed.